Оптимизационная эконометрическая модель межотраслевого баланса - Лавров, Л.Г.; Карпец, Э.П. (Теорія оптимальних рішень, 2005)
An econometric model of interindustry balance is propoat, that assumes computation of statistical dependence between its defined indices on the basis of processing of dynamical rows of an actual information. 0he model optimization solution criterion is the requirement of maximum population demand satisfaction.